Projects : assessment resource kit - Forster, Margaret; Masters, Geoff (Camberwell, Vic : Australian Council for Educational Research, 1996)
What is project assessment? A focus on process. A focus on end product. When comparability matters. Designing project assessments. A summary of the project design process.
Keywords: Education; Teaching; Activity programs in education -- Australia; Project method in teaching